Investigation of the mechanical properties of lignin nanofibrous structures using statistical modeling. Issue 17 (September 2018) - Hosseini, Seyed Abdolkarim; Lin, Li-Ting; Ko, Frank
The growing use of nanomaterials, environmental concerns and related industrial applications have provided unique opportunities for the development of nanofibers from natural biopolymers such as lignin. The main purpose of this study was to develop a direct relationship between lignin single nanofiber, the aligned nanofiber mat and the twisted nanofiber yarn's strength using the weakest link theory of strength and the statistical model proposed for parallel fiber bundles. Twisted yarn strength was obtained via in situ mechanical properties of yarn constituent nanofibers affected by the Weibull distribution parameters, fiber fragmentation phenomenon, and obliquity. The results showed that the estimated strength of the single nanofiber and the aligned nanofiber mat was in a good agreement with the experimental data. As it might be expected, the yarn's estimated strength was found to be highly influenced by the fiber fragmentation phenomenon.